2011
DOI: 10.1007/s00360-011-0631-x
|View full text |Cite
|
Sign up to set email alerts
|

Warming up for dinner: torpor and arousal in hibernating Natterer’s bats (Myotis nattereri) studied by radio telemetry

Abstract: The frequency and function of arousals during hibernation in free-living mammals are little known. We used temperature-sensitive radio transmitters to measure patterns of torpor, arousal and activity in wild Natterer's bats Myotis nattereri during hibernation. Duration of torpor bouts ranged from 0.06 to 20.4 days with individual means ranging from 0.9 to 8.9 days. Arousals from torpor occurred most commonly coincident with the time (relative to sunset) typical for bats emerging from summer roosts to forage. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 64 publications
(83 reference statements)
2
55
1
Order By: Relevance
“…The difference in winter climate between the two sites could partially explain differences. Aerial insect abundance can decrease dramatically with decreasing T a (Jones et al., 1995), and T a  < 10°C has often been reported to constrain insect abundance (Hope & Jones, 2012; Park, Jones, & Ransome, 2000). During winter, mean night T a in Hauturu (12.1 ± 2.4°C) is higher than Pureora (6.2 ± 2.7°C), mean night T a  > 10°C occurred on 92% of observation nights in Hauturu compared to 7% in Pureora, and T a never dropped below 0°C in Hauturu but did so on 26% of nights in Pureora (Czenze, Brigham, Hickey, & Parsons, 2017a).…”
Section: Discussionmentioning
confidence: 99%
“…The difference in winter climate between the two sites could partially explain differences. Aerial insect abundance can decrease dramatically with decreasing T a (Jones et al., 1995), and T a  < 10°C has often been reported to constrain insect abundance (Hope & Jones, 2012; Park, Jones, & Ransome, 2000). During winter, mean night T a in Hauturu (12.1 ± 2.4°C) is higher than Pureora (6.2 ± 2.7°C), mean night T a  > 10°C occurred on 92% of observation nights in Hauturu compared to 7% in Pureora, and T a never dropped below 0°C in Hauturu but did so on 26% of nights in Pureora (Czenze, Brigham, Hickey, & Parsons, 2017a).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies of torpor and hibernation in free-ranging mammals report on parameters associated with T b or skin temperature (T sk ) such as torpor bout duration or minimum torpid T sk (Hope and Jones, 2012;Michener, 1992;Munro et al, 2005;Park et al, 2000) but the commodity of interest for these studies is energy (Brigham et al, 2011;Willis, 2007). Estimates of hibernation energy requirements are important for answering fundamental and applied questions about hibernation, such as identifying crucial winter habitats for bats, and predicting impacts of disturbance, disease, yearto-year variation in weather patterns or climate change Boyles and Willis, 2010;Frick et al, 2010;Humphries et al, 2002;Landry-Cuerrier et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…LandryCuerrier et al, 2008;Michener, 1992;Munro et al, 2005), only a handful of studies of thermoregulation during hibernation exist for free-ranging bats and many of these are for tropical or sub-tropical species (Cory Toussaint et al, 2010;Liu and Karasov, 2010;Stawski et al, 2009;Turbill, 2006;Turbill and Geiser, 2008). Very few studies have reported long-term body temperature profiles of temperate-zone bats in winter (Hope and Jones, 2012;Park et al, 2000). Temperate-zone bats may spend energy reserves differently from rodents during hibernation.…”
Section: Introductionmentioning
confidence: 99%
“…This paper therefore proceeds through accounts of encounters with swarming bats and results from bat detection surveys between summer 2010 and winter 2011. Reflections on the embodied practice of detection are entwined with successful experiments in technological attunement, achieved through ongoing ecological monitoring of swarming and a study of hibernal ecology at Greywell Tunnel (see Hope and Jones, 2012). The threatened status of many European bat populations is concerning and demands action.…”
Section: Introducing Bats: Field Site and Methodsologymentioning
confidence: 98%
“…The study of hibernators in these climates is of particular relevance in light of climatic induced environmental change, whilst the devastating effect of the fungal pathogen Geomyces destructans on hibernating bats in North America (Frick et al, 2010) has highlighted the need for a better understanding of torpor patterns in wild bat populations. Research conducted by Hope and Jones (2012) sought to better understand the frequency of arousal from torpor in Natterer's bats, and investigate if one reason for arousal on winter nights is to take advantage of foraging opportunities.…”
Section: Trackingmentioning
confidence: 99%